2004
DOI: 10.1242/dev.00907
|View full text |Cite
|
Sign up to set email alerts
|

Death is the major fate of medial edge epithelial cells and the cause of basal lamina degradation during palatogenesis

Abstract: During mammalian development, a pair of shelves fuses to form the secondary palate, a process that requires the adhesion of the medial edge epithelial tissue (MEE) of each shelf and the degeneration of the resulting medial epithelial seam (MES). It has been reported that epithelialmesenchymal transformation (EMT) occurs during shelf fusion and is considered a fundamental process for MES degeneration. We recently found that cell death is a necessary process for shelf fusion. These findings uncovered the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
218
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(237 citation statements)
references
References 45 publications
14
218
1
4
Order By: Relevance
“…In contrast to the few studies of the lip fusion process, the fate of the medial edge epithelial (MEE) cells of the secondary palatal shelves, which form the midline epithelial seam upon palatal shelf adhesion, has been studied extensively although considerable disagreement still exists. TEM and cell biological studies have provided clear evidence of apoptosis of at least a portion of the MEE cells (Glucksmann, 1965;Saunders, 1966;DeAngelis and Nalbandian, 1968;Smiley and Dixon, 1968;Shapiro and Sweney, 1969;Smiley and Koch, 1975;Mori et al, 1994;Taniguchi et al, 1995;Cuervo et al, 2002;Cuervo and Covarrubias, 2004). Others, however, reported that the midline epithelial seam cells looked healthy at the TEM level and found evidence of transdifferentiation of MEE cells into mesenchymal cells by using various cell labeling techniques (Fitchett and Hay, 1989;Shuler et al, 1991Shuler et al, , 1992Griffith and Hay, 1992;Sun et al, 1998;Martinez-Alvarez et al, 2000;Nawshad et al, 2004).…”
Section: Is Programmed Cell Death Emt or Both The Mechanism Involvementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the few studies of the lip fusion process, the fate of the medial edge epithelial (MEE) cells of the secondary palatal shelves, which form the midline epithelial seam upon palatal shelf adhesion, has been studied extensively although considerable disagreement still exists. TEM and cell biological studies have provided clear evidence of apoptosis of at least a portion of the MEE cells (Glucksmann, 1965;Saunders, 1966;DeAngelis and Nalbandian, 1968;Smiley and Dixon, 1968;Shapiro and Sweney, 1969;Smiley and Koch, 1975;Mori et al, 1994;Taniguchi et al, 1995;Cuervo et al, 2002;Cuervo and Covarrubias, 2004). Others, however, reported that the midline epithelial seam cells looked healthy at the TEM level and found evidence of transdifferentiation of MEE cells into mesenchymal cells by using various cell labeling techniques (Fitchett and Hay, 1989;Shuler et al, 1991Shuler et al, , 1992Griffith and Hay, 1992;Sun et al, 1998;Martinez-Alvarez et al, 2000;Nawshad et al, 2004).…”
Section: Is Programmed Cell Death Emt or Both The Mechanism Involvementioning
confidence: 99%
“…Others, however, reported that the midline epithelial seam cells looked healthy at the TEM level and found evidence of transdifferentiation of MEE cells into mesenchymal cells by using various cell labeling techniques (Fitchett and Hay, 1989;Shuler et al, 1991Shuler et al, , 1992Griffith and Hay, 1992;Sun et al, 1998;Martinez-Alvarez et al, 2000;Nawshad et al, 2004). Because large numbers of apoptotic cells in the fusing epithelial seam were only observed in palatal explant cultures (Martinez-Alvarez et al, 2000;Cuervo et al, 2002;Cuervo and Covarrubias, 2004), Nawshad et al (2004) and Hay (2005) , 1997). However, the loxP-flanked transcription STOP cassette prevents the lacZ gene from being transcribed in the R26R mice (Soriano, 1999).…”
Section: Is Programmed Cell Death Emt or Both The Mechanism Involvementioning
confidence: 99%
See 1 more Smart Citation
“…There is strong evidence that disruption of the palatal epithelial seam during palatal fusion results at least in part from apoptosis (Cecconi et al, 1998;Cuervo and Covarrubias, 2004;Martinez-Alvarez et al, 2004;Vaziri Sani et al, 2005). We carried out terminal deoxynucleotidyl transferasemediated deoxyuridinetriphosphate nick end-labeling (TUNEL) analysis to investigate the mechanism involved in the disruption of the epithelial seam between the palate and tongue in the Jag2 ⌬DSL/⌬DSL mutants and found that the palate-tongue seam contained numerous apoptotic cells, similar to the wild-type palate-palate seam during palatal fusion (Fig.…”
Section: Analysis Of Jag2 Mutants Provides Support For the Role Of Tgmentioning
confidence: 99%
“…The process of palatal fusion has been studied extensively, but there is still disagreement over the relative contributions of epithelial-mesenchymal transformation versus apoptosis to the disappearance of the epithelial seam (Fitchett and Hay, 1989;Cuervo and Covarrubias, 2004;reviewed in Nawshad et al, 2004). Those favoring epithelial-mesenchymal transformation as the major mechanism propose that apoptosis is restricted to the periderm layer and suggest that this is important for the initial adhesion of the palatal shelf epithelia.…”
Section: Molecular and Cellular Mechanisms Underlying The Aberrant Ormentioning
confidence: 99%